Organizational Conference of Tuvan Regional Branch of the Liberal Economic Society of Russia - Kylgydai, Ai-Kys Ch. (The New Research of Tuva, 2011)
Article tells about the Organizational Conference of Tuvan Regional Branch of the Liberal Economic Society of Russia that was held on June 8, 2011 with a managerial personnel being elected.